The Effect of Nosocomial Infection on the Severity and Outcome of the Disease in Patients with Severe and Extremely Severe COVID-19 - L. M. Kalmanson; I. V. Shlyk; Yu. S. Polushin; O. V. Stanevich; A. A. Galkina (Вестник анестезиологии и реаниматологии, 2022)
The mechanisms of development of nosocomial infectious complications in COVID-19 and the contribution of bacterial and mycotic superinfection to the formation of extremely high mortality among patients with severe and extremely severe course of this disease have not yet been fully revealed. The objective: to study epidemiology, risk factors for the development of nosocomial superinfection, and its effect on the severity and outcome of the disease in patients with COVID-19.Subjects and Methods. 383 cases of severe and extremely severe COVID-19 were retrospectively analyzed. Demographic data, the presence of concomitant diseases, community-acquired co-infection at the time of hospitalization, data on the methods used to treat new coronavirus infection, severity of the course of the disease, developed infectious complications and their etiology, and the disease outcome were studied. Risk factors for the development of secondary infectious complications and the contribution of nosocomial superinfection to the severity of COVID-19 and the disease outcome were evaluated.Results. Risk factors for the development of secondary infectious complications include age over 65 years (OR 1.04; 95% CI 1.03–1.06; p < 0.0001), concomitant cardiovascular pathology (OR 3.82; 95% CI 2.02‒7.19; p < 0.0001), chronic kidney disease, including requiring renal replacement therapy (OR 2.01; 95% CI 1.33–3.02; p = 0.0007), and glucocorticoid therapy (OR 1.62; 95% CI 1.02–2.69; p = 0.04). The development of nosocomial infectious complications in patients with COVID-19 is associated with a more severe course of the disease and unfavorable prognosis (OR 13.44; 95% CI 8.23‒21.92; p < 0.0001).Conclusion. Identification of risk factors for the development of secondary infectious complications in COVID-19 allows developing differentiated approaches to the pathogenetic treatment of patients with severe COVID-19, increasing alertness in terms of the development of nosocomial infections, ensuring their timely diagnosis and treatment.